Analysis of Some of the Unanswered Questions That the Labour Collective Bargaining Presents Under the Framework of the Spanish Public Administration - Carlos Arroyo (Central European Public Administration Review)
The collective bargaining over working conditions of employees in the Public Administration service finds a number of features that in some cases do not always have a clear legal protection and in others, they have some specific characteristics exclusively in the public sector, thus making it necessary to proceed to its analysis.